Acute kidney injury as the presenting feature of sarcoidosis - Mehta, Sudhir; Singh, Akashdeep; Makkar, Vikas (African Journal of Nephrology, 2021)
Acute kidney injury is rarely the presenting feature of sarcoidosis. We report the case of a patient whose diagnosis was brought to light by the investigation of impaired kidney function. Concurrent hypercalcaemia was noted and prompted further investigation, which led to the diagnosis of sarcoidosis. This is a rare phenomenon and is an important consideration in the patient with acute kidney injury and hypercalcaemia, without an apparent explanation. Rapid improvement in both kidney function and hypercalcaemia occurred in response to treatment.